Some Challenges for Organizing Sustainable Cultural Events - Dimitrova, Vesselina (Research Papers, 2021)
The article attempts to analyze the main steps ahead for organizing sustainable cultural events with the idea of assessing some trends and challenges. Using a descriptive and analytical approach, the author presents a brief empirical case study of some economic, social and environmental aspects regarding the organization of sustainable cultural events in Bulgaria, according to the Global Reporting Initiative framework.  The author summarizes that the information awareness of cultural operators in Bulgaria is still at basic reporting level and it needs a relatively easy approach to implement and analyze sustainability data.
Keywords: Global Reporting initiative; Sustainable cultural events